Topiramate Therapy and Cognitive Dysfunction - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The effects of topiramate (TPA) adjunctive therapy on cognition in 22 consecutive patients with intractable epilepsy were studied at the Montreal Neurological Hospital, Quebec, Canada.